Enhanced photocatalytic-biological degradation of 2,4 dichlorophenoxyacetic acid - Reham Samir; Tamer Essam; Yasser Ragab; Abdelgawad Hashem (Faculty of Pharmacy, Cairo University, 2015)
2,4-Dichlorophenoxyacetic acid (2,4-D) is the third most commonly used herbicide all over the world. There is a contradicted opinion about its toxicity and its half life in the environment. In this study the most effective method of its degradation and bioremediation has been studied. Two microbial consortia capable of utilizing 2,4-D as a sole source of carbon were isolated from the Egyptian environment. One of the microbial consortia interestingly contained a certain kind of protozoa as one of the mixed consortia members. Degradation of 2,4-D by the microbial consortia was affected by 2,4-D initial concentration, agitation, pH of the medium and temperature. The two consortia were able to degrade up to 700 mg l−1 of 2,4-D. Pre-treatment with UV radiations in the presence of photocatalyst such as TiO2 accelerates the biodegradation process. The toxic non biodegradable concentration of 2,4-D which was found to be the 800 mg l−1, was degraded by pre-treatment with UV/TiO2 and a subsequent microbial inoculation. The combined treatment proved to be an efficient mean of biodegradation and detoxification of toxic non biodegradable concentrations of 2,4-D.